2001
DOI: 10.1002/pip.372
|View full text |Cite
|
Sign up to set email alerts
|

Purification of metallurgical‐grade silicon up to solar grade

Abstract: An estimate has been made of the feasibility of a metallurgical puri®cation process, the NEDO (New Energy and Industrial Technology Development Organization) melt-puri®cation process, for manufacturing solar-grade silicon from metallurgical-grade silicon. Equipment has been developed to pilot manufacturing plant scale. The system comprises an electron-beam furnace for phosphorus removal and a plasma furnace for boron removal. Each furnace has a mold for directional solidi®cation to remove metallic impurities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(78 citation statements)
references
References 2 publications
5
69
0
4
Order By: Relevance
“…They concluded that the highest water vapor pressure, 1.24 vol.% H 2 O, has the highest apparent rate constant for boron removal. Similar experiments were carried out by Nakamura et al 7 and Yuge et al 8 Recently, Wu et al 10 reported their experimental results for the removal of boron by an Ar-H 2 O-O 2 mixture. Boron was reduced from 18 ppm to 2 ppm after the first 10 min.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…They concluded that the highest water vapor pressure, 1.24 vol.% H 2 O, has the highest apparent rate constant for boron removal. Similar experiments were carried out by Nakamura et al 7 and Yuge et al 8 Recently, Wu et al 10 reported their experimental results for the removal of boron by an Ar-H 2 O-O 2 mixture. Boron was reduced from 18 ppm to 2 ppm after the first 10 min.…”
Section: Introductionsupporting
confidence: 68%
“…A comparison of the apparent mass transfer coefficients between the current work and those of steam-added plasma melting processes [5][6][7][8] is shown in Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The removal of B from silicon by gas treatment has been studied by several researchers using plasma technique or gas blowing. The application of H 2 O gas in the reactive gas in plasma refining [1][2][3][4][5][6] and H 2 -H 2 O gas mixtures through non-plasma-aided gas blowing [7,8] has shown faster B removal compared to the application of pure H 2 , [8][9][10] O 2 , [9,11] and CO 2 [11] as reactive gases. The plasma refining experiments with H 2 -O 2 mixtures [12,13] as the reactive gas have also indicated faster B removal from silicon than using H 2 , O 2 , CO 2 gases.…”
Section: Introductionmentioning
confidence: 99%
“…They try to upgrade the metallurgical silicon through a combination of steps suited for the different impurities. For example, by directional solidification they take advantage of the high liquid-solid segregation coefficient of metallic impurities; by leaching they eliminate metallic suicides in the grain boundaries; by slagging, gas blowing, evaporation and plasma torch they try to reduce the concentration of boron and/or phosphorus;... [11] [12] [13].…”
Section: Applying Typical Steps From Metallurgical Refinementmentioning
confidence: 99%